2023
DOI: 10.1590/1519-6984.247609
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal ultrasound in amazonian manatee (Trichechus inunguis) (Natterer, 1883)

Abstract: Morphophysiological species researches are fundamental, and diagnostic imaging is an excellent technique, already used in wild animals, with great application, not invasive and provide real-time information of each body. Amazonian manatees are on the list of endangered animals classified in the vulnerable category and knowledge of the normal pattern of ultrasound anatomy of organs and tissues is important for the maintenance and well-being of captive specimens contributing to reintroduction actions. The object… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Despite this, we found that lactate & Walsh (2018) suggested that lactate dehydrodehydrogenase values in the Colombian popula-genase is helpful in the clinical assessment of tion were below the ranges obtained for the same manatees, specifically in cases of watercraft colsubspecies in Puerto Rico and for the Amazonian lisions or gastrointestinal disorders. However, it Harvey et al, 2018;Barreto et al, Antillean, and Florida manatees (Table 7). While 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite this, we found that lactate & Walsh (2018) suggested that lactate dehydrodehydrogenase values in the Colombian popula-genase is helpful in the clinical assessment of tion were below the ranges obtained for the same manatees, specifically in cases of watercraft colsubspecies in Puerto Rico and for the Amazonian lisions or gastrointestinal disorders. However, it Harvey et al, 2018;Barreto et al, Antillean, and Florida manatees (Table 7). While 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The high levels of blood urea nitrogen found may findings with the implementation of complete be due to a high protein intake in the diet such hematology and blood chemistry tests, urinalysis, as the case of Amazonian manatees artificially coprology, and imaging aids (Harvey et al, 2007;nursed with milk (Sousa et al, 2016). However, Barreto et al, 2021;Cabrias-Contreras et al, it is essential to highlight that high levels of urea 2021; Thrall et al, 2022). nitrogen in manatees above the reference values Triglyceride levels in the Colombian populamay be associated with prerenal azotemia second-tion coincided with those reported for the Antillean ary to diuresis and hemoconcentration, which can subspecies.…”
Section: Proteinsmentioning
confidence: 99%
“…are aquatic mammals classified as "vulnerable" by the International Union for Conservation of Nature (IUCN) (MARMONTEL et al, 2016). There are two species of the manatee in Brazil, the American manatee (T. manatus) and the Amazonian manatee (T. inunguis), both of which are threatened by hunting, accidental capture, and destruction of their natural habitats (BARRETO et al, 2021;CABALLERO et al, 2021;SIDRIM et al, 2015). To reduce the impact of these threats, orphaned American manatee calves, victims of poaching, or those accidentally caught in fishing nets were rescued at various locations in Amazonas State (Brazil) and rehabilitated at the National Institute for Amazonian Research (INPA).…”
Section: Introductionmentioning
confidence: 99%